Ideology: Factors of Middle East Conflict and Failure - Khaled Ibrahim (GoAcademica Research & Publishing, 2020)
The following article explains how Western ideology is a major factor in the occurrence of conflicts and state failures in the Middle East. In this paper, the author looks at the perspective of ideological hegemony. Ideology destroys the political and economic system which causes social inequality, thus accelerating the outbreak of conflict in the Middle East. The author raises Syria and Libya as examples to prove the factors driving the conflict. The author argues that the main cause of the Middle East conflict is the influence of Western ideology that has not been accepted by both the holders of power and society, which has led to divisions and even wars. Democracy is a model that is accepted in many countries which cannot be applied in the Middle East. The author also criticizes the failure to implement democracy and liberal economics in the Middle East.